Open source Content Management Systems (CMS): Issues and challenges - Elgharabawy, Mohamed Ahmed; Ayu, Media Anugerah (IIUM Press, 2011)

(untitled)
There are over 800 online CMS available nowadays. Some of them are free whereas others are meant for commercial usage. Despite the popularity that CMS have gained over the past years, still there are many issues that need to be addressed when it comes to CMS. These issues face all users or developers who intend to use CMS. However, these issues were not comprehensively studied in the texts reviewed. This article is trying to highlight the issues and challenges that are mostly faced when using an open source CMS. This analysis is based on article reviews as well as trials of different CMS.